The Implementation and Challenges of Performance Based Authentic Assessment in Descriptive Text Reading Comprehension at SMAN 1 Padang Panjang - Neni Afrida Sari Harahap; Putri Litania Sitinjak (CV. PUSDIKRA MITRA JAYA, 2026)
This study aims to investigate the implementation of performance-based authentic assessment in descriptive text reading comprehension and to identify the challenges faced by students at SMAN 1 Padang Panjang. This research employed a descriptive qualitative design, with data collected from ten tenth-grade students through a reading task and a questionnaire as the main data sources. The reading task consisted of a descriptive text followed by open-ended comprehension questions, while the questionnaire was distributed via Google Form to explore students’ difficulties in reading activities. The instruments used in this study were a reading comprehension task and a structured questionnaire, and the data were analyzed using descriptive qualitative analysis to interpret students’ responses and identify common patterns of difficulties. The findings revealed that performance-based authentic assessment was implemented through meaningful tasks requiring students to construct their own responses based on text comprehension. Most students achieved high scores, with an average of 85%, indicating generally good comprehension ability; however, several challenges were identified, particularly in understanding new vocabulary, identifying the main idea, and comprehending long sentences. Despite these challenges, students were generally able to understand the overall meaning of the text. The study implies that performance-based authentic assessment is effective in evaluating students’ reading comprehension in a more meaningful way, but its success depends on students’ vocabulary knowledge and reading strategies; therefore, teachers are recommended to provide vocabulary support and explicit instruction on reading strategies to improve students’ performance in authentic assessment tasks.